ENHANCE CYBER NOTARY FOR BUYERS ONLINE BUYING AND SALE - Henry Aspan; Etty Sri Wahyuni; Ari Prabowo; Ami Natuz Zahara (Jurnal Ekonomi, 2023)
This study aims to determine the major role of Cyber Notary for a Notary in issuing Certificate Authorithy as an effort to protect the law for buyers in online buying and selling transactions, as well as the process of making evidence so that it can be used as authentic evidence. This research was conducted using a statutory approach and also using a conceptual approach. The type of data used is secondary data in the form of sources of legal materials. Data collection techniques used by way of literature study. The verification process requires digital forensics and can be verified through the office of the Ministry of Law and Human Rights of the Republic of Indonesia by scanning a barcode directly. The position of a Notary should accommodate and involve a Notary in issuing electronic certificates, so this role should also be regulated in the Law on the Position of a Notary. Included in the changes to the Electronic Information and Transaction Law, The position of a Notary should be recognized as a service provider in the electronics field, so that it can serve as protection for the parties in buying and selling online. The process of making evidence so that it can be categorized as authentic evidence should be regulated in law to become reinforcement and can be used as authentic evidence.